Corpus callosal microstructure influences intermanual transfer in chimpanzees - Phillips, Kimberley A.; Schaeffer, Jennifer A.; Hopkins, William D. (Frontiers in Systems Neuroscience, 2013)
Learning a new motor skill with one hand typically results in performance improvements in the alternate hand. The neural substrates involved with this skill acquisition are poorly understood. We combined behavioral testing and noninvasive brain imaging to study how the organization of the corpus callosum was related to intermanual transfer performance in chimpanzees. Fifty-three chimpanzees were tested for intermanual transfer of learning using a bent-wire task. Magnetic resonance and diffusion tensor images were collected from 39 of these subjects. The dominant hand showed greater performance benefits than the non-dominant hand. Further, performance was associated with structural integrity of the motor and sensory regions of the CC. Subjects with better intermanual transfer of learning had lower fractional anisotropy values. The results are consistent with the callosal access model of motor programming.